Multidisciplinary Collaboration in the Development of Teaching Aids and Learning at SDN 8 Juli - Noviyanti; Sri Novayanti; Zalikha; Fajrinur (STMIK Indonesia Banda Aceh, 2025)
This community service program aimed to develop instructional teaching aids through multidisciplinary collaboration between lecturers and students from various study programs at Universitas Islam Kebangsaan Indonesia (UNIKI). The activity was conducted at SDN 8 Juli, an elementary school located in a rural area of Bireuen Regency, Aceh, which faces limitations in concrete learning media. The development process adopted the ADDIE model (Analysis, Design, Development, Implementation, Evaluation), allowing the creation of teaching aids to be carried out systematically and participatively. Based on a needs analysis, it was found that students experienced difficulties in understanding abstract concepts in science and English subjects. To address this challenge, the team designed several innovative teaching aids, including a volcanic eruption model, a rain cycle diorama, bilingual science vocabulary cards, and thematic student worksheets (LKS). These media were then implemented in thematic learning activities in Grades III and V. The implementation results indicated improvements in conceptual understanding, learning motivation, and student participation. Teachers also expressed enthusiasm and a willingness to use the media independently in the future. The evaluation, carried out through classroom observation and teacher reflection, showed that the developed media were relevant to classroom needs and easy to apply. This program demonstrated that cross-disciplinary collaboration can produce effective and sustainable learning media. The model is recommended for replication in other elementary schools, particularly those located in areas with limited educational resources.